MY SAY: Neuroeconomics, anyone? - Abd Razak, Dzulkifli (2008)
Reaganomics, Freakonomics, Enronomics — this is how malleable economics is or, rather, the uncertainty surrounding it, especially in the wake of the prevailing financial meltdown. And suddenly, there is one other option to chose from — Obamanomics. Not surprisingly, some regard economics as a "pseudoscience", made popular only recently. No matter, economics apparently rules our lives. After all, "Reaganomics" is about changing lifestyles to accommodate the course of an economic policy imposed by the Reagan administration. We are helpless to resist.